Implikasi Hijab Terhadap Pendidikan Akhlaq - Titin Nurhidayati; M Nafiur Rofiq (STAIFAS-Press, 2020)
In the development of science and technology, especially information technology, it is not followed in the field of morals. The world is getting more advanced, but on the other hand, humans are increasingly backward. Man succeeded in achieving his goals in the world, but he failed to think about his fate in the hereafter. The fall of a nation and state in any age has never occurred due to an intellectual crisis, but generally due to a moral crisis. A country no matter how poor and backward it is can still be guaranteed to survive, if the morals of the implementers of the State and its people are not damaged. Morals have a very important role in determining life and relationships. The phenomenon of using the hijab today has shifted its meaning, so that the hijab is not only a cover for aurat according to Islamic law, but now it has become a fashion for some Muslim women to impress or present a religious atmosphere in the life they live.